Without compass or map cultural organizations, different dialogues - Katyal, Anjum; Kishore, Naveen; Conference of Asian Foundations and Organizations (Calcutta Seagull Books, 2004)
An attempt to highlight dialogues on traditional, contemporary arts, socio-economic and media in the form of cultural exchange among seven Asian countries.
"Conference of Asian Foundations and Organizations."
Keywords: Associations, institutions, etc. -- Asia -- Case studies; Cultural relations -- Case studies; Arts -- Asia -- Societies, etc. -- Case studies; Ethnology -- Asia -- Societies, etc. -- Case studies